2017
DOI: 10.1016/j.celrep.2017.06.076
|View full text |Cite
|
Sign up to set email alerts
|

Polycomb Responds to Low Levels of Transcription

Abstract: SUMMARY How is Polycomb (Pc), a eukaryotic negative regulator of transcription, targeted to specific mammalian genes? Our genome-wide analysis of the Pc mark H3K27me3 in murine cells that revealed Pc is preferentially associated with CpG island promoters of genes that are transcribed at a low level, and less so with promoters of genes that are either silent or more highly expressed. Studies of the CpG island promoter of the Kit gene demonstrate that Pc is largely absent when the gene is silent in myeloid cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 38 publications
2
19
0
Order By: Relevance
“…Since a comprehensive assessment of this is currently out of reach (due to the lack of extensive genome-wide binding data for most regulatory factors), we focused on EZH2 as a proof-ofprinciple. EZH2 is a relatively well-characterized histone methylstransferase that specifically localizes to CpG islands of non-transcribed genes (Figure 3a, Supplemental Figure S8; Riising et al (2014) and Berrozpe et al (2017)). We discovered that tissue-specific genes with CpGdense and EZH2-bound promoters (EZH2 binding in at least 2 ENCODE experiments) have lower LOEUF compared to their EZH2-unbound counterparts (Figure 3b; regression β = −5.66, p = 5.21 · 10 −8 , for the interaction between CpG density and EZH2 binding, conditional on tissue specificity τ > 0.6).…”
Section: Regulatory Factor Binding At Promoters Provides Information mentioning
confidence: 99%
“…Since a comprehensive assessment of this is currently out of reach (due to the lack of extensive genome-wide binding data for most regulatory factors), we focused on EZH2 as a proof-ofprinciple. EZH2 is a relatively well-characterized histone methylstransferase that specifically localizes to CpG islands of non-transcribed genes (Figure 3a, Supplemental Figure S8; Riising et al (2014) and Berrozpe et al (2017)). We discovered that tissue-specific genes with CpGdense and EZH2-bound promoters (EZH2 binding in at least 2 ENCODE experiments) have lower LOEUF compared to their EZH2-unbound counterparts (Figure 3b; regression β = −5.66, p = 5.21 · 10 −8 , for the interaction between CpG density and EZH2 binding, conditional on tissue specificity τ > 0.6).…”
Section: Regulatory Factor Binding At Promoters Provides Information mentioning
confidence: 99%
“…In hyperacetylated chromatin, TF-binding motifs previously cryptic in heterochromatin become exposed and can trap TFs, reducing their free concentration and consequently their availability for binding to enhancers (Model formalized in the S.I.). Then, E-H3K27 methylases like polycomb could complete the system by methylating poorly occupied E-H3K27, as verified in [59], thus precluding their reacetylation.…”
Section: Hypothetical Origin Of Bivalent Chromatinmentioning
confidence: 88%
“…They are strongly upregulated in the TSA treatment by 22-and 19-fold for SNAI1 and SNAI2 respectively, and in cancer, such as during the mammary hormonal escape, where the SNAI repress ERα and E-cadherin [61]. Another excellent molecular candidate for repressing differentiation genes after chromatin opening is the polycomb system mentioned above, which could simply validate the lower occupancy of enhancers by TFs [59] (model in the S.I.) and proceed to their closure.…”
Section: Why Some Genes Are Repressed In the Context Of Globally Openmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a recent study using genome-wide ChIP-seq and transcription profiles in murine cells showed that H3K27me3 was enriched at genes with low levels of expression and depleted at completely silenced genes, and highly expressed genes [78] . We were prompted to investigate whether the chromatin features at PcTF-activated genes might reflect a low to moderate expression state.…”
Section: Pctf-sensitive Interferon Response Genes Are Shared Across Tmentioning
confidence: 99%